The Effect of Mastery of Writing Theory and Writing Motivation on Writing Practices - TRIDINANTI, GAYA; RONI, RUSMAN; SARI, FARNIA; NURULANNINGSIH, NURULANNINGSIH (Universitas Jambi, Indonesia, 2020)
ABSTRACT : The purpose of this study to determine the correlation among writing theory, writing motivation and the writing practice of narrative text. The method used is survey with correlational techniques. The analytical method used is correlational analysis. The population is all students of English Department. The sample is 75 students with total sampling technique. The result shows that (1) there is significant correlation between Writing Theory and Writing Practice, proven by t value = 5.579 and Sig0.000 <0.05;(2) there is significant correlation between Writing Motivation and Writing Practice, proven by t value = 2.167 and Sig. 0.000 <0.05; (3) there is significant contribution of Writing Theory and Writing Motivation toward Writing Practice, proven by Fo = 64.936 and Sig. 0.000 <0.05. It can be concluded that the writing practice of narrative text is correlated by writing theory and writing motivation both partially and simultaneously. Keywords: motivation, narrative text, practice, theory, writing